2016
DOI: 10.1159/000446025
|View full text |Cite
|
Sign up to set email alerts
|

NET Blood Transcript Analysis Defines the Crossing of the Clinical Rubicon: When Stable Disease Becomes Progressive

Abstract: Background/Aims: A key issue in gastroenteropancreatic neuroendocrine tumors (GEP-NETs) is early identification and prediction of disease progression. Clinical evaluation and imaging are limited due to the lack of sensitivity and disease indolence. We assessed the NETest as a predictive and prognostic marker of progression in a long-term follow-up study. Methods: GEP-NETs (n = 34) followed for a median 4 years (2.2-5.4) were evaluated. WHO tumor grade/stage grade 1: n = 17, grade 2: n = 14, grade 3: n = 1 (for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
129
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(152 citation statements)
references
References 52 publications
17
129
0
2
Order By: Relevance
“…NETest levels have been reported to be of value in defining SD and PD [18, 19]. In this study, we identified significantly ( p < 0.0001) higher levels in PD (mean: 61) than SD (mean: 35).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…NETest levels have been reported to be of value in defining SD and PD [18, 19]. In this study, we identified significantly ( p < 0.0001) higher levels in PD (mean: 61) than SD (mean: 35).…”
Section: Discussionsupporting
confidence: 55%
“…It has been suggested that measurement of transcript levels before and after BPC surgery will facilitate early identification of residual or recurrent disease prior to imaging. This has been demonstrated to be the case in gastroenteropancreatic NET disease [18]. …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To better reflect not only the mere secretory activity but also the complex biologic activities of an evolving neoplasm (cell proliferation, growth factor signaling, and others) that constitute the hallmarks of cancer, and to provide more relevant information on tumor behavior, new approaches have been introduced, including whole-genome sequencing, circulating micro-RNA, and tumor transcripts (60). Evaluation of circulating messenger RNA (transcript analysis) has provided information on disease status that is of substantial clinical utility in the management of NENs (61,62). This strategy uses simultaneous polymerase chain reaction-based analyses of multiple neuroendocrine tumor genes measurable in the blood and algorhythmic transformation into a mathematic index of disease activity (60,63).…”
Section: Integration Within the Diagnostic Algorithm Of Nensmentioning
confidence: 99%
“…I am not only concerned and interested in making novel drugs possible for patients but also interested in clinical research related to prognostic factors in NET including novel biomarkers to predict disease progression (Hilfenhaus et al 2013, Pavel et al 2016. One of my research projects supported by the DKTK (Deutsches Konsortium für Translationale Krebsforschung, German Cancer Foundation, Heidelberg) focuses on the evaluation of a mutational panel for prognostic purpose.…”
Section: :11mentioning
confidence: 99%